The Efficacy of a Multidisciplinary Group Program for Patients with Refractory Chronic Pain - Masayuki Inoue; Shinsuke Inoue; Tatsunori Ikemoto; Young-Chang P Arai; Masatoshi Nakata; Atsuko Miyazaki; Makoto Nishihara; Takashi Kawai; Noboru Hatakeyama; Setsuko Yamaguchi; Kazuhiro Shimo; Hirofumi Miyagawa; et al. (Pain Research and Management)
BACKGROUND: Chronic pain is a major problem because it can result in not only a reduction in activities of daily living and quality of life but also requires initiation of social assistance. Seeking only to eliminate pain itself would appear to be too narrow an objective, in addition to often being unachievable; therefore, a multifaceted, comprehensive approach with multiple objectives is needed.